jPopGen Suite: population genetic analysis of DNA polymorphism from nucleotide sequences with errors - Liu, Xiaoming (2012)
1. Next-generation sequencing (NGS) is being increasingly used in ecological and evolutionary studies. Though promising, NGS is known to be error-prone. Sequencing error can cause significant bias for population genetic analysis of a sequence sample. 2. We present jPopGen Suite, an integrated tool for population genetic analysis of DNA polymorphisms from nucleotide sequences. It is specially designed for data with a non-negligible error rate, although it serves well for “error-free” data. It implements several methods for estimating the population mutation rate, population growth rate, and conducting neutrality tests. 3. jPopGen Suite facilitates the population genetic analysis of NGS data in various applications, and is freely available for non-commercial users at http://sites.google.com/site/jpopgen/.